Clientelistic politics and pro-poor targeting: Rules versus discretionary budgets - Dilip Mookherjee; Anusha Nath (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Past research has provided evidence of clientelistic politics in delivery of programme benefits by local governments, or gram panchayats (GPs), and manipulation of GP programme budgets by legislators and elected officials at upper tiers in West Bengal, India. Using household panel survey data spanning 1998-2008, we examine the consequences of clientelism for distributive equity. We find that targeting of anti-poverty programmes was progressive both within and across GPs and is explained by greater 'vote responsiveness' of poor households to receipt of welfare benefits. Across-GP allocations were more progressive than those of a rule-based formula recommended by the Third State Finance Commission based on GP demographic characteristics. Moreover, alternative formulae for across-GP budgets obtained by varying weights on GP characteristics used in the State Finance Commission formula would have only marginally improved pro-poor targeting. Hence, there is not much scope for improving pro-poor targeting of private benefits by transitioning to formula-based budgeting.
Keywords: H40; H75; H76; P48; 330; clientelism; governance; targeting; budgeting